Influence of energy fraction in EDM drilling of Inconel 718 by statistical analysis and finite element crater-modelling. (April 2019) - Kliuev, Mikhail; Florio, Kevin; Akbari, Mansur; Wegener, Konrad
Graphical abstract: Highlights: The increase of discharge pulse duration rises the workpiece fraction of energy. The increase of discharge current reduces the workpiece fraction of energy. Marangoni effect does not have a significant influence on the final crater shape. Influence of temperature-dependent properties essential for EDM crater simulation. Abstract: An increase of productivity of electro discharge machining (EDM) is crucial for industrial applications. Energy losses minimisation in plasma-material interaction influences the material removal rate (MRR) in the EDM process. The energy distribution in EDM drilling is the factor that has to be analysed and optimized in order to achieve high-performance machining, reduce costs and increase the quality of the machined parts. In the present work, finite element analysis (FEA) of a single discharge is performed to calculate the energy fraction flowing into the anode. Computational fluid dynamics (CFD) simulations with Marangoni effect and considering the temperature dependent material properties are performed. Inverse FEA is performed in order to calculate the fraction of the energy distributed into the workpiece using a measured crater shape as an input parameter of the model. The model considers as an input the measured current, voltage and final shape of a single crater. The resulting energy fraction is achieved by the fitting of the single discharge modelling parameters to the experiments with various erosion parameters. It is shown that the discharge current is the parameter, which has the biggest impact on the fraction of energy distributed into the workpiece. Longer discharge time increases the fraction of energy distributed into the anode. However, it is proved that longer discharge time is positively correlated with the crater diameter growth. The results of the simulation also showed that the Marangoni effect does not have a significant impact on the removed material, but it affects the shape of the crater. Furthermore, it is proven that in FEA the influence of the temperature dependent material properties in solids and fluids is up to 24% on the estimation of the crater depth.